Improved exercise ventilatory efficiency with nasal compared to oral breathing in cardiac patients - Eser, Prisca; Calamai, Pietro; Kalberer, Anja; Stuetz, Laura; Huber, Sarina; Kaesermann, Dominic; Guler, Sabina; Wilhelm, Matthias (Frontiers in Physiology, 2024)
To assess whether nasal breathing improves exercise ventilatory efficiency in patients with heart failure (HF) or chronic coronary syndromes (CCS).Exercise inefficient ventilation predicts disease progression and mortality in patients with cardiovascular diseases. In healthy people, improved ventilatory efficiency with nasal compared to oral breathing was found.Four study groups were recruited: Patients with HF, patients with CCS, old (age≥45 years) and young (age 20 to 40 years) healthy control subjects. After a 3-min warm-up, measurements of 5 min with once nasal and once oral breathing were performed in randomized order at 50% peak power on cycle ergometer. Ventilation and gas exchange parameters measured with spiroergometry were analysed by Wilcoxon paired-sample tests and linear mixed models adjusted for sex, height, weight and test order.Groups comprised 15 HF, CCS, and young control and 12 old control. Ventilation/carbon dioxide production (V ̇E/V ̇CO2), ventilation (V ̇E), breathing frequency (fR), and end-tidal oxygen partial pressure (PETO2) were significantly lower and tidal volume and end-tidal carbon dioxide partial pressure (PETCO2) significantly higher during nasal compared to oral breathing in all groups, with large effect sizes for most parameters. For patients with HF, median V ̇E/V ̇CO2 was 35% lower, with nasal compared to oral breathingfR 26% lower, and PETCO2 10% higher with nasal compared to oral breathing, respectively. in 14 of 15 patients with HF and 13 of 15 patients with CCS. Exercise oscillatory ventilation (EOV) was present in 6 patients and markedly reduced with nasal breathing.Nasal breathing during submaximal exercise significantly improved ventilatory efficiency and abnormal breathing patterns (rapid shallow breathing and EOV) in 80% of our patients with HF and CCS.